Pengaruh Profitabilitas dan Permodalan terhadap Efisiensi Bank Konvensional di Indonesia - Erika Febiyanti; Justina Ade Judiarni (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of profitability and capital adequacy on the efficiency of conventional banks in Indonesia during the period of 2021–2024. This study employed a quantitative approach using secondary data obtained from the financial statements of conventional banks registered with the Financial Services Authority (OJK). The sample was selected using purposive sampling, resulting in 86 banks that met the research criteria during the observation period. Data analysis was conducted using panel data regression with the assistance of EViews 12 software. Based on the results of the Chow Test and Hausman Test, the Fixed Effect Model (FEM) was selected as the most appropriate model. The findings indicate that profitability proxied by Return on Assets (ROA) has a negative and significant effect on the Operating Expenses to Operating Income ratio (BOPO). This result implies that higher profitability contributes to lower BOPO values and consequently improves the operational efficiency of conventional banks in Indonesia. Meanwhile, capital adequacy, proxied by the Capital Adequacy Ratio (CAR) has a positive but insignificant effect on BOPO indicating that an increase in capital has not been able to significantly improve bank efficiency. This finding suggests that adequate capital levels are not necessarily accompanied by the bank's ability to reduce operational costs more efficiently. Simultaneously, profitability and capital adequacy significantly affect the efficiency of conventional banks in Indonesia.